2010
DOI: 10.1080/14616690903042724
|View full text |Cite
|
Sign up to set email alerts
|

Political Economy of Informalization

Abstract: This article has two main aims. The first is to problematize the dominant view of the informal economy as a sort of separate economy, related primarily to (immigrant) small business and distinct from the socalled formal economy, which for the most part encompasses big companies as well as state economic activities. In contrast, the present article assumes that all economic actors are increasingly ready to adopt informal economic strategies to secure their economical survival. In line with this assumption, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
211
0
14

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(225 citation statements)
references
References 47 publications
0
211
0
14
Order By: Relevance
“…Until now, some limited evidence exists to support this marginalization thesis when studying the informal economy. Studies have shown informal employment to be concentrated among those more likely to be excluded from the formal labour market, including the unemployed (Brill 2011;Slavnic 2010;Taiwo 2013) and women (ILO 2013;Leonard 1994;Stănculescu 2004). However, other studies reveal that the unemployed are not more likely to participate (Williams 2001), and that men are more likely to participate (Lemieux, Fortin, and Frechette 1994;McInnis-Dittrich 1995).…”
Section: Explaining Unregistered Employment: Theoretical Framing and mentioning
confidence: 99%
“…Until now, some limited evidence exists to support this marginalization thesis when studying the informal economy. Studies have shown informal employment to be concentrated among those more likely to be excluded from the formal labour market, including the unemployed (Brill 2011;Slavnic 2010;Taiwo 2013) and women (ILO 2013;Leonard 1994;Stănculescu 2004). However, other studies reveal that the unemployed are not more likely to participate (Williams 2001), and that men are more likely to participate (Lemieux, Fortin, and Frechette 1994;McInnis-Dittrich 1995).…”
Section: Explaining Unregistered Employment: Theoretical Framing and mentioning
confidence: 99%
“…Certains auteurs soulignent également l'existence d'un lien entre le secteur informel et la corruption ainsi que le crime organisé (Ponsaers, Shapland et Williams, 2008). Un discours différent s'est développé en économie politique (voir Williams, 2015) qui considère le travail informel plutôt comme une conséquence d'un manque d'intervention de l'État dans le marché du travail, des processus de dérégulation, de privatisation et de libéralisation (Castells et Portes, 1989 ;Sassen, 1996 ;Slavnic, 2010 ;Taiwo, 2013). Dans cette perspective, l'emploi informel est caractérisé par une forme de travail à bas salaire, sans protection sociale, fourni principalement par des couches marginalisées de la population qui y recourent comme stratégie de survie.…”
Section: éTats-providence Et Travail Informelunclassified
“…From this standpoint, informal employment is a central facet of de-regulated global capitalism and integral component of the new sub-contracting, outsourcing and downsizing practices which provide a channel through which businesses can achieve flexible production, profit and cost reduction (Castells and Portes, 1989;Davis, 2006;Gallin, 2001;Sassen, 1996;Slavnic, 2010;Taiwo, 2013). As such, informal employment is seen as a survival practice to which marginalised populations turn out of necessity as a last resort when alternative means of livelihood are absent and as composed of 'sweatshop-like' dependent employment and/or 'false' self-employment (Ahmad, 2008;Geetz and O'Grady, 2002;Ghezzi, 2010).…”
Section: Explaining the Prevalence Of Informal Employment: The Neo-limentioning
confidence: 99%